Permeability and selectivity study for polyethersulfone membrane for gas separation - Zuriah, Ismail (2009)
An symmetric polyethersulfone (PES) membrane were prepared through a dry/wet phase inversion process. The casting solution developed in this research consisted of PES, 1-methyl-2-pyrolidone (NMP) and methanol. The turbidity test was carried out to find an ideal weight percentage of casting solution. Membrane composition of 22.28 wt% and 26.58 wt% of PES was used for permeability test. PES membrane was divided into three categories; uncoated, coated with polydimethylsiloxane (PDMS) and coated with bromine solution. Permeation test was carried out by testing CO2, CH4, N2 and O2 permeating through the membrane to check the permeability and selectivity of the respective gas to CH4. Different coating agent gave different rate of permeate while higher polymer concentration increased the permeation rate. The PES membrane coated with PDMS showed higher selectivity compared to uncoated membrane and membrane coated with bromine solution. The selectivity of CO2/CH4 was approximately 2.77, at 26.58wt% of PES concentration coated with 3wt% of PDMS. It was believed that different coating agent strongly affects the membrane performance as well as the polymer concentration.